Appreciative Inquiry in the Workplace: A Review of (Quasi) Experimental Studies - Miglianico, Marine; Dubreuil, Philippe; Miquelon, Paule; Bakker, Arnold B.; Martin‐Krumm, Charles (John Wiley & Sons, 2026)
The objective of this study is to review the literature of (quasi) experimental studies on appreciative inquiry (AI) in the workplace. We present an overview of the AI approach, a summary of four main purported AI outcomes in organizations (generativity, engagement and performance, team-oriented behaviours, and virtuousness and flourishing), and a literature review of (quasi) experimental studies on AI in the workplace. Results of (quasi) experimental studies suggest that AI can positively influence team-oriented behaviours and performance, but may have no specific effect on generativity. Practical implications as well as avenues for future research are discussed.
Keywords: appreciative inquiry; experimental design; intervention; longitudinal design; review; work; fi=Henkilöstöjohtaminen|en=Human Resource Management|